Tracing Loss and Gain in Translating Ambiguity and Culture in Shakespeare’s Macbeth from English to Arabic - Hamed, Halima; Mehiri, Ramdane; Behar, Mohamed Mostefa (LANGUAGE ART, 2025)
Ambiguity is a rhetorical device closely tied to the culture of the source text (ST). It plays a primordial role in the literary text as it adds profundity, suspense as well as harmony and unity. Poets employ it to communicate both language and culture; however, translating the literary text’s ambiguity is not of that ease. Ambiguity creates many difficulties due to linguistic and cultural differences of the source text (ST) and target text(TT), what causes a big loss in meaning during transfer. In order to preserve both the aesthetic form and the suspense ambiguity creates, this paper follows a qualitative method and relies on Lawrence Venuti’s approaches in translating literary texts. By comparing selected passages from Jabra Ibrahim Jabra (2008) with Amin Hussein Ahmed (1994) Arabic translations of Shakespeare’s Macbeth, the study explores the main strategies translators adopt to avoid loss in meaning and culture. The analysis reveals that in order to avoid loss in translation, translators have to rely on specific strategies such as: literal translation, domestication and neutralization to preserve the text’s communicative purpose to the target reader, and make their translations faithful to the source text. Moreover, it demonstrates the validity of translating culturally specific terms through domestication, adaptation and neutralization. The study also offers readers two main strategies based on Venuti model: Domestication and foreignization.